Pelatihan Seni Tari sebagai Upaya Pengembangan Kreativitas dan Kepercayaan Diri Anggota Dharma Wanita SMAN 1 Surade - Gina Ressa Anisa Senja; Jaeni Jaeni; Yahfenel Evi Fussalam (CV. ALIM'SPUBLISHING, 2026)
Abstract Women play an important role in social and community life; however, opportunities for self-expression and personal development through artistic activities are still limited, particularly within community organizations. This community service program aimed to enhance the creativity and self-confidence of Dharma Wanita members at SMAN 1 Surade through dance training activities. The program involved nine participants and was conducted over approximately one month, culminating in a cultural arts performance on February 04, 2026. The method used was participatory training consisting of preparation, implementation, and evaluation stages. The training activities included basic dance movement introduction, movement practice with musical accompaniment, movement exploration, group choreography arrangement, and performance simulation. Data were collected through observation, interviews, and documentation. The findings showed that participants experienced increased creativity in developing movement variations and expressing ideas through dance. In addition, participants demonstrated higher levels of self-confidence, particularly in performing publicly during the cultural arts event. The program also strengthened social interaction, cooperation, and solidarity among participants. Therefore, dance training can serve as an effective arts and culture-based strategy for women’s empowerment and self-development in community environments. Keywords: dance training; creativity; self-confidence; women empowerment; community service